Methodological Approach to the Definition of a Blockchain System for the Food Industry Supply Chain Traceability - Bettín-Díaz, Rafael; Rojas, Alix E.; Mejía-Moncayo, Camilo (Computational Science and Its Applications - ICCSA 2018, 2018)
In this paper, we present a novel methodology to integrate the Blockchain technology in the food industry supply chain to allow traceability along the process and provide the ultimate customer with enough information about the origin of the product to make an informed purchase decision. This methodology gathers the best practices in marketing, process engineering and the technology itself, alongside with the authors’ experience during its application in the organic coffee industry in the Colombian market. The Authors extracted the best out of the best practices and made it simple for anyone interested in its uses and application. The result is a simple and easy methodology that suits any product, supply chain, and required system configurations; due to its versatility and adaptability.